Foreign exchange intervention as a monetary policy instrument : evidence for inflation targeting countries - Hüfner, Felix (Heidelberg : New York : Physica-Verlag, 2004)
This book contributes to closing this gap between theory and practice by interpreting foreign exchange intervention as an additional monetary policy instrument for inflation targeting central banks. In-depth empirical analyses of the foreign exchange operations and interest rate policy of five inflation targeting countries (Australia, Canada, New Zealand, Sweden and the United Kingdom) demonstrate how foreign exchange intervention is used in practice.
Includes bibliographical references (p. [167]-175).
oif 19/08/15
Loans
Keywords: Foreign exchange administration; Banks and banking, Central; Banks and banking, International; Inflation targeting